Szkoła wobec wyzwań współczesności - socjopedagogiczny model optymalizacji szans życiowych dzieci i młodzieży = School towards the contemporary challenges - a sociopedagogical model of optimising the children and youth?s life opportunities - Mosiek, Piotr (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Polish contemporary school, being constantly subject to reform, now faces a difficult task of preparing students to their functioning in a dynamically changing reality. Apart from the tasks in the field of education and care, it also seems crucial to perform the pro-employment function. The introduced article takes the sociopedagogical stand, in which strong emphasis is put on social support for students (pro-social activity of the institution) and treating altruism as a crucial pedagogical task.
Keywords: system edukacyjny; działalność prozatrudnieniowa szkoły; rynek pracy; wsparcie społeczne; altruizm; społeczności lokalne; educational system; pro-employment activity of school; labour market; social support; altruism; local community